New Surgical Technique to Induce Reversible Liver Fibrosis by Surgical Closure of Major Duodenal Orifice in Dogs - Marwan Khalil; Ahmed Ali (مجلة الانبار للعلوم البيطرية)
This study was conducted to induce and evaluate reversible liver fibrosis in dogs by surgical closure of the major duodenal orifice. The study was performed on six healthy local adult dogs. Reversible liver fibrosis was surgically induced in all animals by surgical closure of major duodenal papilla using absorbable suture material for 60 days. Induced liver fibrosis was assessed by clinical, ultrasonographical examination, laboratory and histological methods. The clinical manifestation of the jaundiced dogs showed reduced food intake, pale-yellowish mucus membrane, inflammatory signs of the wound site and severe postoperative pain. Biochemically, there was significantly increased values of the aspartate aminotransferase, alkaline phosphatase, alanine aminotransferase, indirect bilirubin, direct bilirubin and total bilirubin especially during the first two days after surgery followed by a gradual decrease of these values until the end of the but still higher than normal values. Ultrasonographic examinations showed abnormal changes in the liver tissue such as an increase in both size and wall thickness of the gall bladder and mottled heterogeneous appearance of the liver during the first two weeks following the surgical induction of the hepatic fibrosis. Histological evaluation of liver samples revealed showed necrosis of hepatocytes and deposition of eosinophilic material, infiltration of inflammatory cells, recent thrombus in the hepatic vein, fatty change. Slight clinical, biochemical, ultrasonographic improvement was observed at 30th post-operative day. In conclusion, surgical induction of reversible liver fibrosis in dogs was an easy technique by surgical closure of major duodenal papilla and the results were confirmed by the clinical, ultrasonographical, laboratory and histological examination.